THE CURRENT SITUATION AND ANALYSIS OF LENDING TO SMALL BUSINESS ENTITIES - J. E. Makhmudov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The purpose of this study is to explore the methods of small business entities to develop small businesses through the use of digital technologies. In this, it was highlighted that the development of lending to small business entities is of great importance, as well as suggestions and recommendations were developed regarding the use of digital technologies in lending to small business entities and their analysis.